Stereochemistry in the Stobbe Condensation - Jabbar, Saba; Banerjee, Shubhra (Asian Journal of Chemistry, 2010)
The diacids obtained from acid-esters 2-carbomethoxy-1-β-naphthyl-4,4-diphenylbutadiene-3-carboxylic acid (3a)and 3-carbomethoxy-1-β-naphthyl-4,4-diphenylbutadiene-2-carboxylic acid (3b) are identical. Also, the diacids obtained from 2-carbomethoxy-1-β-naphthyl-4,4-methyl, phenylbutadiene-3-carboxylic acid (3d) and 3-carbomethoxy-l-β-naphthyl- 4,4-methyl, phenylbutadiene-3-carboxylic acid (3e) are identical. The physico-chemical properties along with the cyclization reactions of the products clearly indicate that the Stobbe condensation of alkylidensesuccinic ester with aryaldehydes invariably leads to the product having trans Ar/COOMe groups.